mozilla

Revision 384839 of Proving the Pythagorean theorem

  • Revision slug: Web/MathML/Examples/MathML_Pythagorean_Theorem
  • Revision title: MathML Pythagorean Theorem
  • Revision id: 384839
  • Created:
  • Creator: fscholz
  • Is current revision? No
  • Comment MathML/Examples/MathML_Pythagorean_Theorem Web/MathML/Examples/MathML_Pythagorean_Theorem

Revision Content

a 2 + b 2 = c 2 We can prove the theorem algebraically by showing that the area of the big square equals the area
of the inner square (hypotenuse squared) plus the area of the four triangles:
(a + b)2 = c2 + 4(1 2)a b a2 + 2ab + b2 = c2 + 2ab a2 + b2 = c2

Revision Source

<math style="font-size: 16pt; font-family: arial; mspace depth="1ex" height="0.5ex" width="2.5ex" side="left" >
  <mtable columnalign="left">
    <mtr>
      <mtd>
        <mrow>
          <mrow>
            <mrow>
                   <mrow>
                   <mspace depth="1ex" height="0.5ex" width="2.5ex"/>
                   
                   <msup>
              <mi>a</mi>
     
              <mn>2</mn>
              </msup>
            </mrow>
            <mo> + </mo>
            <msup>
              <mi>b</mi>
     
              <mn>2</mn>
              </msup>
                   <mo> = </mo>
                   <msup>
              <mi>c</mi>
              <mn>2</mn>
              </msup>
    
        </mrow>
      </mtd>
    </mtr>
    
    <mtr>
      <mtd>
        <mrow>
          <mrow>
            <mrow>
                 
                   <mspace depth="1ex" height="0.5ex" width="2.5ex"/>
                   <mrow><mtext mathcolor="black" mathsize="12pt">
                   We can prove the theorem algebraically by showing that the area of the big square equals
                   the area<br /> of the inner square (hypotenuse squared) plus the
                   area of the four triangles: </mtext>  
                   </mrow>  
                   
                   </mrow>
        </mrow>
                   
        </mrow>
        
      </mtd>
    </mtr>
    <mtr>
      <mtd>
        <mrow>
          <mrow>
            <mrow>
                   <mrow>
                   <mspace depth="1ex" height="0.5ex" width="2.5ex"/>
         <mo>(</mo><mi>a</mi><mo> + </mo>
                     <mi>b</mi><msup><mo>)</mo><mn>2</mn></msup><mo> = </mo>
                   <msup><mi>c</mi><mn>2</mn></msup><mo> + </mo>
                   <mn>4</mn><mo>(</mo><mfrac><mrow><mn>1</mn></mrow>
               <mn>2</mn></mfrac><mo>)</mo><mi>a</mi>
                   <mi>b</mi>
                     </mrow>
                     </mrow>
      </mtd>
    </mtr>
    
    <mtr>
      <mtd>
        <mrow>
          <mrow>
            <mrow>
                   <mrow>
                   <mspace depth="1ex" height="0.5ex" width="2.5ex"/>
         <msup><mi>a</mi><mn>2 </mn></msup><mo> + </mo>
                     <mn>2</mn><mi>a</mi><mi>b</mi><mo> + </mo><msup><mi>b</mi><mn>2 </mn></msup>
                   <mo> =</mo>
                   <msup><mi>c</mi><mn>2</mn></msup><mo> + </mo>
                   <mn>2</mn><mi>a</mn><mi>b</mi>

                     </mrow>
                     </mrow>
      </mtd>
    </mtr>
    
    
     <mtr>
      <mtd>
        <mrow>
          <mrow>
            <mrow>
                   <mrow>
                   <mspace depth="1ex" height="0.5ex" width="2.5ex"/>
         <msup><mi>a</mi><mn>2 </mn></msup><mo> + </mo>
                     <msup><mi>b</mi><mn>2</mn></msup>
                   <mo> =</mo>
                   <msup><mi>c</mi><mn>2</mn></msup>
                     </mrow>
                     </mrow>
      </mtd>
    </mtr>
    
    
  </mtable>
</mrow>
</math>
Revert to this revision